An Ecological Approach for the Integration of Sustainability into the Accounting Education and Professional Practice - Sisaye, Seleshi (Advances in Management Accounting, 2012)
The organizational ecology perspective approaches the integration of sustainability into the accounting curriculum by following the evolutionary process of organizational development. There is a growing interest in sustainability, and, recently, books and articles have appeared that discuss sustainability accounting and reporting. A number of schools have developed standalone courses in sustainability accounting while others have integrated sustainability into existing courses in accounting ethics or corporate social responsibility. This chapter applies ecological, both organizational sociological and anthropological, approaches to argue in favor of integration of sustainability into the accounting curriculum rather than in standalone courses. These two approaches are utilized because these disciplines have well-established theoretical and methodological approaches that can be applied to study the subject of sustainability, natural resources conservation, and ecological management. In addition, the current trend in accounting education is for the incorporation of social and behavioral sciences perspectives, including sociology and anthropology, into the accounting curriculum. Accordingly, the application of the ecological approach from these disciplines contributes significantly to the study of the integration of sustainability into the accounting curriculum.